Instrumen Kompetensi Profesional Guru Matematika Terintegrasi Nilai-Nilai Pendidikan Agama Islam - Zamsiswaya; Giantara , Febri (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2024)
Abstract One of the problems with mathematics education in Indonesia can be seen from the fact that there are not many mathematics teachers who explain mathematics material that is integrated with the values ​​of Islamic Religious Education. In order to measure the professional competence of mathematics teachers, an instrument is needed. The professional competency instruments for mathematics teachers used so far do not fully contain the values ​​of Islamic Religious Education in their aspects and indicators. Therefore, it is necessary to develop a professional competency instrument for mathematics teachers that is integrated with the values ​​of Islamic Religious Education. The development method used is ADDIE. Data collection and data analysis techniques use quantitative and qualitative approaches. This research was conducted at SMA Tapung District with a sample size of 210 obtained using the Issac Michael formula. From the results of research and development and product trials, a valid and reliable mathematics teacher professional competency instrument was obtained so that it can be used. Keywords: Professional competence, integration, Islamic education Abstrak Permasalahan pendidikan matematika di Indonesia salah satunya dapat dilihat dari belum banyaknya guru matematika yang menjelaskan materi matematika yang terintegrasi nilai-nilai Pendidikan Agama Islam. Agar dapat mengukur kompetensi profesional guru matematika dibutuhkan sebuah instrumen. Instrumen kompetensi profesional guru matematika yang digunakan selama ini belum sepenuhnya memiliki nilai-nilai Pendidikan Agama Islam pada aspek dan indikatornya. Oleh sebab itu diperlukan pengembangan sebuah instrumen kompetensi profesional guru matematika yang terintegrasi nilai-nilai Pendidikan Agama Islam. Metode pengembangan yang digunakan adalah ADDIE. Teknik pengumpulan data dan analisis data menggunakan pendekatan kuantitatif dan kualitatif. Penelitian ini dilakukan di SMA Kecamatan Tapung dengan jumlah sampel 210 yang diperoleh dengan menggunakan rumus Issac Michael. Hasil penelitian dan pengembangan hingga uji coba produk diperoleh sebuah instrument kompetensi profesioanal guru matematika yang valid dan reliabel sehingga dapat untuk digunakan. Kata Kunci: Kompetensi profesional, integrasi, Pendidikan Agama Islam.